Decidability of Circumscribed Description Logics Revisited - Bonatti, Piero; Faella, Marco; Lutz, Carsten; Sauro, Luigi; Wolter, Frank (Advances in Knowledge Representation, Logic Programming, and Abstract Argumentation, 2015)
We revisit non-monotonic description logics based on circumscription (with preferences) and prove several decidability results for their satisfiability problem. In particular, we consider circumscribed description logics without the finite model property (DL-Lite $_{\mathcal{F}}$ and $\mathcal{ALCFI}$ ) and with fixed roles (DL-Lite $_{\mathcal{F}}$ and a fragment of DL-Lite $_{\mathcal{R}}$ ), improving upon previous decidability results that are limited to logics which have the finite model property and do not allow to fix roles during minimization.